2022
DOI: 10.1101/2022.06.11.495646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Separation of transcriptional repressor and activator functions in HDAC3

Abstract: The histone deacetylase HDAC3 is associated with the NCoR/SMRT co-repressor complex and its canonical function is in transcriptional repression, but it can also activate transcription. Here we show that the repressor and activator functions of HDAC3 can be genetically separated in Drosophila. A lysine substitution in the N-terminus (K26A) disrupts its catalytic activity and activator function, whereas a combination of substitutions (HEBI) abrogating the interaction with SMRTER enhance repressor activity beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 57 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…Consistent with our observations, previous studies have shown that HDAC3 plays a deacetylase-independent role in inhibiting extracellular matrix scaffold protein expression during mouse heart development, mediated by the transforming growth factor-βpathway [14]. Consistently, deacetylase-dead mutation K26A still maintain the repressor activity of HDAC3 during embryo development in Drosophila [24]. So we speculated that the non-enzymatic role of HDAC3 is involved in maintaining adult heart function through inhibiting ECM protein Pericardin in Drosophila.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our observations, previous studies have shown that HDAC3 plays a deacetylase-independent role in inhibiting extracellular matrix scaffold protein expression during mouse heart development, mediated by the transforming growth factor-βpathway [14]. Consistently, deacetylase-dead mutation K26A still maintain the repressor activity of HDAC3 during embryo development in Drosophila [24]. So we speculated that the non-enzymatic role of HDAC3 is involved in maintaining adult heart function through inhibiting ECM protein Pericardin in Drosophila.…”
Section: Discussionsupporting
confidence: 91%
“…The crystal structure of HDAC3 revealed that K25 residue is a key residue that contacts the DAD domain of NCoR/SMRT [9,10,23]. HDAC3 harboring a K25A mutation disrupted the deacetylase activity [12].The corresponding HDAC3 K26A mutation in Drosophila also disrupted deacetylase activity [24]. To investigate if the cardiac phenotype in HDAC3 KD is dependent on the deacetylase activity, we generated wild type or deacetylase-dead mutant HDAC3 transgenic flies under its own endogenous promoter.…”
Section: Deacetylase Dead Hdac3 Mutants Rescue Both Cardiac Physiolog...mentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding HDAC3 K26A mutation in Drosophila also disrupted deacetylase activity (Min Tang et al, 2022). To investigate if the cardiac phenotype in HDAC3 KD is dependent on the deacetylase activity, we generated WT or deacetylase-dead mutant HDAC3 transgenic flies under its own endogenous promoter.…”
Section: Deacetylase-dead Hdac3 Mutants Rescue Both Cardiac Physiolog...mentioning
confidence: 99%
“…To investigate if the cardiac phenotype in HDAC3 KD is dependent on the deacetylase activity, we generated WT or deacetylase-dead mutant HDAC3 transgenic flies under its own endogenous promoter. The transgene was mutated at the RNA interference targeting sites by using a synonymous coden to resist shRNA targeting, hereafter referred to as shRNA-resistant transgene (Min Tang et al, 2022).…”
Section: Deacetylase-dead Hdac3 Mutants Rescue Both Cardiac Physiolog...mentioning
confidence: 99%